Primitive off-rift basalts from Iceland and Jan Mayen: Os-isotopic evidence for a mantle source containing enriched subcontinental lithosphere - Debaille, Vinciane; Tronnes, R. G.; Brandon, A.D; Waight, T. E.; Graham, D. W.; Lee, C.-T.A. (2009)
info:eu-repo/semantics/published